Acupuncture Synergized With Bortezomib Improves Survival of Multiple Myeloma Mice via Decreasing Metabolic Ornithine - Ke, Mengying; Qian, Jinjun; Hao, Feng; Li, Xinying; Wu, Hongjie; Luo, Xian; Xu, Bin; Gu, Chunyan; Yang, Ye (Frontiers in Oncology, 2021)
Multiple myeloma (MM) is a hematological malignancy worldwide in urgent need for novel therapeutic strategies. Since Velcade (bortezomib) was approved for the treatment of relapsed/refractory MM in 2003, we have seen considerable improvement in extending MM patient survival. However, most patients are fraught with high recurrence rate and incurability. Acupuncture is known for alleviating patient symptoms and improving the quality of life, but it is not well investigated in MM, especially in combination with bortezomib. In this study, we employed LC-MS and UHPLC-MS together with bioinformatics methods to test blood samples from 5TMM3VT MM murine model mice with four different treatments (control (C) group, bortezomib (V) treatment group, acupuncture (A) group and combined (VA) group). MM mice in group VA had longer survival time than mice in group A or group V. Joint pathway analysis indicated the underlying arginine and proline metabolism pathway among the 32 significantly decreased metabolites in group VA. CCK-8 assay and in vivo experiments validated that ornithine, the metabolite of arginine, promoted MM cell proliferation. In addition, gene expression omnibus (GEO) database analysis suggested that MM patients with higher ornithine decarboxylase 1 (ODC1) expression were evidently associated with poor overall survival. In summary, this study demonstrates the synergistic effects of acupuncture and bortezomib on extending the survival of MM model mice and provides potential therapeutic targets in the treatment of MM.